A 'surprising and mature portrait'? Reflecting on representations of mental illness in Rookie Blue. Issue 2 (1st October 2015) - Brown, Shane
In 2006, an article in the Journal of Health Communication called for a collaboration between the mental health sector in America and the media industries in order 'to counter negative portrayals of mental illness, and to explore the potential for positive portrayals to educate and inform, as well as to entertain'. Eight years on, there has been an increase in the portrayals of mental illness in popular North American television drama series. This article focuses on the police procedural drama Rookie Blue (2010–) and the narrative arc in season four which concerns a policewoman with bipolar disorder. This is an autoethnographical article, giving a personal reaction to the portrayal of a condition I have had for twenty years, and the ways in which such portrayals can contribute to the stigmas surrounding mental illness.